Online counselling session : developing ethical guideline framework for counsellors and clients in Malaysia - Zulfikar bin Ahmad (Kulliyah of Education, International Islamic University Malaysia, 2017)
The advancement of technology offers a new communication medium and approach for counsellors in Malaysia to deliver counselling sessions online. Although the traditional practice of counselling involves face-to-face interaction between counsellor and client, a growing number of practitioners are providing online counselling sessions via Social Networking Services (SNS) and Mobile Chat Applications (MCA). The goal of the study was to develop an ethical guideline framework in an online counselling session for counsellors in Malaysia. Variables such as mutual trust framework, techniques in counselling and ethical guidelines were assessed. Respondents were selected through purposive sampling involving 39 undergraduate students (35 females and 4 males) majoring in Guidance and Counselling from the Kulliyyah of Education, International Islamic University Malaysia (IIUM). The respondents do not represent the whole population but assisted the researcher to pursue Focus Group Discussion (FGD) as the method in collecting data. The processes and procedures of collecting data involved defining a focus group, setting questions, conducting the discussions and analysing the data were properly conducted with the supervision of the respective lecturer in the field. Atlas.ti 7 Window software was used as a tool to analyse data. The results of the study indicated that there are three main elements that help form ethical guidelines in an online counselling session; general ethics of both the counsellor and the client, the counsellor's ethics as the main provider of the service and the users of the services provided. Based on the research finding, a framework on ethical guidelines formed through emerging topics was proposed. Guidelines on confidentiality and security, dual relationship and informed consent ethics when conducting online counselling session were identified as core elements in the ethical framework proposed. The implication and contributions of the finding may help to assist counsellors, clients, the government, higher learning institutions and accreditation bodies in providing better counselling services in the future.